The orphan's song - Kate, Lauren (G.P. Putnam's Sons, 2019)
Venice, 1736. When fate brings Violetta and Mino together on the roof of the Hospital of the Incurables, they form a connection that will change their lives forever. Both are orphans at the Incurables, dreaming of escape. But when the resident Maestro notices Violetta's voice, she is selected for the Incurables' world famous coro, and must sign an oath never to sing beyond its church doors. After a declaration of love ends in heartbreak, Mino flees the Incurables in search of his family. Known as the "city of masks," Venice is full of secrets, and Mino is certain one will lead to his long-lost mother. Without him, the walls close in on Violetta and she begins a dangerous and forbidden nightlife, hoping her voice can secure her freedom. But neither finds what they are looking for, until a haunting memory Violetta has suppressed since childhood leads them to a shocking confrontation.